2016
DOI: 10.1089/jwh.2015.5318
|View full text |Cite
|
Sign up to set email alerts
|

Young Women's Perceptions of the Relationship inFifty Shades of Grey

Abstract: Our findings point to the value of using popular culture, including the Fifty Shades narrative, to actively engage young women in productive conversation about characteristics of relationship health and un-health. Similar approaches could be used to engage young women in safe, relatable conversations about healthy and unhealthy relationships, including the warning signs of abuse. As a broader impact, our study contributes to an understanding of how young women interact with and make sense of relationships depi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In our experience as college instructors, some students struggle to name abuse in popular media, such as in the situation where Chris Brown assaulted Rihanna (Stephens & Eaton, 2016) and in popular film such as Fifty Shades of Grey (Bonomi, Nichols, Carotta, Perry, & Kiuchi, 2015), even when what is depicted meets legal definitions of sexual or relationship violence. We anticipate that the use of the Abuse Litmus Test will assist students with identifying when a relationship crosses the line to being abusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experience as college instructors, some students struggle to name abuse in popular media, such as in the situation where Chris Brown assaulted Rihanna (Stephens & Eaton, 2016) and in popular film such as Fifty Shades of Grey (Bonomi, Nichols, Carotta, Perry, & Kiuchi, 2015), even when what is depicted meets legal definitions of sexual or relationship violence. We anticipate that the use of the Abuse Litmus Test will assist students with identifying when a relationship crosses the line to being abusive.…”
Section: Resultsmentioning
confidence: 99%
“…Given the associations between exposure to popular culture depicting violence against women and corresponding violence‐related risks (Bonomi et al, ; Coyne et al, ; Hernandez et al, ; Vandenbosch & Eggermont, ; Ward, ; Ward & Friedman, ), developing tools to facilitate college students' detection of power, control, and harm in on‐screen relationships may increase awareness and dialogue about relationship abuse and sexual assault. Indeed, some research has already shown that pedagogical approaches using popular film can open dialogue with college students about sexual violence, power, and control in relationships (Bonomi, Nichols, Carotta, Perry, & Kiuchi, ).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…(for a review, see Jeong, Cho, & Hwang, 2012, for a meta-analysis of media literacy interventions), suggesting it maybe an effective component in DV prevention efforts. In fact, violence prevention efforts have acknowledged the importance of being critical consumers of media (Bonomi, Nichols, Carotta, Kiuchi, & Perry, 2016). The inclusion of media literacy in DV programming to help viewers understand how the media influences expectations about appropriate behavior and the acceptability of aggression in dating relationships to resolve conflict should be explored further, to help viewers become aware of the socializing role of media and distinguish between truthful and misleading media messages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a young woman faces pressure to behave as per her family's expectations and while this is a state of oppression, it is considered to be an acceptable and benign social norm. What we understand and practise as dating is also taught to us by movies, music, books and other forms of art and media that are consumed by society in the form of entertainment (Bonomi, Nichols, Carotta, Kiuchi, & Perry, 2016;Bowen et al, 2013;Ismail et al, 2007;Luft et al, 2012;Srdarov & Bourgault du Coudray, 2016). We are thus taught through entertainment and by society 'how' to perceive dating and related behaviours and 'whether' to acknowledge certain behaviours at all, therefore our individuality in attributing meanings to dating and dating violence, is severely limited.…”
Section: Social Constructionismmentioning
confidence: 99%